AGILE FROM FIRST PRINCIPLES - Girvan, Lynda (BCS, THE CHARTERED INSTIT, 2022)
This book is an introductory guide to agile principles, values and mindset that will equip individuals and teams, regardless of role, to apply Agile from first principles. Practical examples are used throughout to bring real-world context to agile theory. This book is ideal for those wanting to achieve the BCS Foundation Certificate in Agile.